Congestion caused by Speed Differences - Erik Verhoef; Jan Rouwendal; Piet Rietveld (Tinbergen Institute, 1997)
In this paper, we investigate congestion caused by differences in desired or possible speeds. Especially outside peak hours, speed differences are probably one of the most important reasons for congestion. Although the model setting, with one lane and no overtaking, may seem simple at first sight, the problemturns out to result easily in quite complicated mathematical expressions. Some main conclusions are that optimal tolls for slow vehicles are higher than those for fast drivers, that the marginal external costs and the optimal tolls for slow drivers are actually decreasing in the equilibrium number of slow drivers, and that `platooning' may become an attractive option especially when the desire for a low speed is caused by a lower value of time.
Keywords: 330; Verkehrsstau; Straßenverkehr; Straßenbenutzungsgebühr; Theorie